Spectral analysis combined with advanced linear unmixing allows for histolocalization of phenolics in leaves of coffee trees - Conéjéro, Geneviève; Noirot, Michel; Talamond, Pascale; Verdeil, Jean-Luc (Frontiers in Plant Science, 2014)
An imaging method using spectral analysis combined with advanced linear unmixing was used to allow histolocalization of natural autofluorescent compounds such as hydroxycinnamic acid (chlorogenic acid) and xanthone (mangiferin) in living cells and tissues (mature coffee leaves). The tested method included three complementary steps: 1/ visualization of natural autofluorescence and spectrum acquisition with a multiphoton microscope; 2/ identification of some compounds using previous information on the chemical composition of the tissue, obtained from litterature; and 3/ localization of candidate compounds by spectral imaging. The second part of the study consisted of describing the histochemical structure of leaves during their development. This revealed very fast histochemical differentiation of leaves during the first week after their emergence. Lastly, young leaves of Coffea pseudozanguebariae (PSE), C. eugenioides (EUG), C. arabica (ARA) and C. canephora (CAN) were compared. This confirmed the presence of xanthone in PSE and EUG, but especially its precise tissue localization. This also highlighted the paternal CAN origin of the leaf structure in the allotetraploid species ARA. The limits and advantages of the method without staining are discussed relative to classical epifluorescence microscopy under UV light. This non-invasive optical technique does not require pretreatment and is an effective experimental tool to differentiate multiple naturally-occuring fluorochores in living tissues.